2021
DOI: 10.1021/acs.orglett.1c02258
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2-Aminoalcohols through Enantioselective Aminoallylation of Ketones by Cu-Catalyzed Reductive Coupling

Abstract: Herein, we report the development of a catalytic enantioselective addition of N-substituted allyl equivalents to ketone electrophiles through use of Cu-catalyzed reductive coupling to access important chiral 1,2-aminoalcohol synthons in high levels of regio-, diastereo-, and enantioselectivity. Factors affecting enantioinduction are discussed including the identification of a reversible ketone allylation step that has not been previously reported in Cu-catalyzed reductive coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…Chiral β-amino alcohols are an important structural motif in many natural products and biologically active compounds, and they serve as a key subunit for chiral auxiliaries, ligands, and catalysts . Several strategies have been developed for the synthesis of enantioenriched β-amino alcohols, including the addition or reduction of chiral amino carbonyls and hydroxyl imines, , ring opening of epoxides, , aminohydroxylation of olefins, reductive coupling of imines with carbonyls, and coupling of α-aminoalkyl radicals with carbonyls . However, few studies have reported the asymmetric synthesis of β-amino tertiary alcohols bearing two α-substituents of similar size, such as two linear alkyl groups.…”
mentioning
confidence: 99%
“…Chiral β-amino alcohols are an important structural motif in many natural products and biologically active compounds, and they serve as a key subunit for chiral auxiliaries, ligands, and catalysts . Several strategies have been developed for the synthesis of enantioenriched β-amino alcohols, including the addition or reduction of chiral amino carbonyls and hydroxyl imines, , ring opening of epoxides, , aminohydroxylation of olefins, reductive coupling of imines with carbonyls, and coupling of α-aminoalkyl radicals with carbonyls . However, few studies have reported the asymmetric synthesis of β-amino tertiary alcohols bearing two α-substituents of similar size, such as two linear alkyl groups.…”
mentioning
confidence: 99%
“…Other notable advances in Cu-catalyzed reactions include the following publications: (1) Cu-catalyzed diazidation reactions; (2) Diastereo-and enantioselective oxidative 1,6-conjugate addition; (3) C–H amination of 8-aminoquinoline-directed ferrocenes; (4) Cu-catalyzed hydroxymethylation of alkynes with formic acid; (5) Cu-catalyzed synthesis of indolyl benzo­[ b ]­carbazoles; (6) Cu-catalyzed tandem cross-coupling and alkynylogous aldol reaction to access exocyclic α-allenols; (7) Tandem Cu- and Rh-catalysis for oxidation of hydrazones and enantioselective cyclopropanation; (8) Cu-catalyzed CF 2 H-substituted 2-amidofurans; (9) Cu-catalyzed annulation of indolyl α-diazocarbonyl to access carbazoles; (10) Cu-catalyzed enantioselective 1,2-reduction of cycloalkenones; (11) Cu-catalyzed enantiodivergent alkynylation of isatins; (12) Cu-catalyzed β-lactam formation from oximes and methyl propiolate; (13) Cu-catalyzed aminosulfonylation of O -homoallyl benzimidates; (14) Cu-catalyzed multicomponent trifluoromethyl­phosphorothiolation of alkenes; (15) Cu-catalyzed chloro-arylsulfonylation of styrene derivatives; (16) Cu-catalyzed synthesis of 5-carboxyl-4-perfluoroalkyl triazoles; (17) Cross-nucleophile coupling of β-allenyl silanes with tertiary C–H bonds to access 1,3-dienes; (18) Cu-catalyzed C­( sp 3 )–H functionalization of O -pentafluorobenzoyl ketone oximes; (19) Total regioselectivity of hydrobromination of alkenes controlled by Fe or Cu catalyst; (20) Enantioselective synthesis of trifluoromethyl cyclopropylboronates by Cu catalysis; (21) Cu-catalyzed asymmetric cyclization of alkenyl diynes; (22) Synergistic Ir/Cu catalysis for asymmetric allylic alkylation of oxindoles; (23) Hydrosilylation of alkynes and alkenes with Cu-photocatalysis under continuous flow conditions; (24) Cu-based water oxidation catalysts with consecutive ligand-based electron transfer; (25) Heteroleptic copper-based complexes for energy-transfer processes: E → Z isomerization and tandem photocatalytic sequences; (26) Copper-catalyzed aminoheteroarylation of unactivated alkenes through distal heteroaryl migration; (27) Copper-catalyzed syntheses of multiple functionalized allenes via three-component reaction of enynes; (28) Unified mechanistic concept of the copper-catalyzed and amide-oxazoline-directed C­(sp 2 )–H bond functionalization; (29) Cu-catalyzed C–H allylation of benzimidazoles with allenes; (30) Synthesis of 1,2-aminoalcohols through enantioselective aminoallylation of ketones by Cu-catalyzed reductive coupling; (31) Copper-catalyzed N-directed distal C­(sp 3 )–H sulfonylation and thiolation with sulfinate salts; and (32) Dehydrogenative aza-[4 + 2] cycloaddition of amines with 1,3-dienes via dual catalysis …”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%
“…In recent decades, considerable attention has been paid to 1,2‐aminoalcohols, [1–5] 1,3‐aminoalcohols, [6–8] and 3‐amino‐1,2‐diols, [9–14] with the latter combining the chemical properties of 1,2‐ and 1,3‐aminoalcohols. These compounds play a crucial role in numerous branches of human life sciences.…”
Section: Introductionmentioning
confidence: 99%